Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 1658994 species occurrences available in GBIF matching the query: { "Geometry" : [ "POLYGON((-94.44397 16.20483,-94.29016 18.11646,-95.23499 18.67676,-96.87195 19.00635,-98.41003 19.33594,-99.29993 18.27026,-99.65149 16.64429,-96.94885 15.63354,-94.44397 16.20483))" ] } The dataset includes 1658994 records from 815 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001830-181108115102211/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences